MAI Journal 2017
DOI: 10.20507/maijournal.2017.6.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Documentary analysis hui: An emergent bricolage method for culturally responsive qualitative research

Abstract: This paper is about the adoption of a novel way of using documentary analysis in order to be culturally responsive in a research setting. It describes an original method, located in an actual empirical study in a wänanga, that meshed the analysis of documents with a group hui through a bricolage approach. To support a Mäori kaupapa, the researcher wished to incorporate values of participation and collaboration, thus overturning the traditional values of simplicity, passivity and individuality that are the purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…This research method is also a way to avoid commitment to traditional research steps, and as results bricolage is also referred to as 'trial of error' (Hammond & Wellington, 2013). For Cardno, Rosales-Anderson, and McDonald (2017), bricolage is all about daring to be different. That said, this method of research is also said to offer a new form of rigor to social research (Kincheloe, 2005), and in some cases, a necessary step toward developing theory (Fincher, Tenenberg, & Robins, 2011).…”
Section: Overarching Methodological Foundationmentioning
confidence: 99%
See 3 more Smart Citations
“…This research method is also a way to avoid commitment to traditional research steps, and as results bricolage is also referred to as 'trial of error' (Hammond & Wellington, 2013). For Cardno, Rosales-Anderson, and McDonald (2017), bricolage is all about daring to be different. That said, this method of research is also said to offer a new form of rigor to social research (Kincheloe, 2005), and in some cases, a necessary step toward developing theory (Fincher, Tenenberg, & Robins, 2011).…”
Section: Overarching Methodological Foundationmentioning
confidence: 99%
“…That said, this method of research is also said to offer a new form of rigor to social research (Kincheloe, 2005), and in some cases, a necessary step toward developing theory (Fincher, Tenenberg, & Robins, 2011). The rigor of bricolage comes from the fact that this research approach uses existing tools, while pushing some boundaries (Cardno et al, 2017). For Cardno et al (2017, p. 150), the boundaries were pushed by incorporating 'the values of respect and participation from Maori Kaupapa into Western research methods to achieve an approach that was culturally responsive'.…”
Section: Overarching Methodological Foundationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although their role in social research is rarely highlighted, it has been observed that documents often serve as key sources of social scientific data (Given, 2008). Documents are one of the main ways of communicating at all levels of society and hence, can provide deep insights into many aspects of life at an organisational or societal level (Cardno et al, 2017). The research design is largely informed by the guidance offered by Bowen (2009), O'Leary (2014) and Bryman (2016).…”
Section: Methodsmentioning
confidence: 99%